Health Care Professionals’ Perceptions of AI in Clinical Practice: Productivity, Enjoyment, and Pay - Michael L Chen; Jiyeong Kim; Mariana Ramirez Posada; David Entwistle; Isabella de Vere Hunt; Yifan Li; Xue Li; Nathanael J Fast; Fatima Rodriquez; Albert Chiou; Euan Ashley; Eleni Linos (JMIR Formative Research, 2026)
Abstract Despite widespread discussion of opportunities and risks about AI in medicine, few health care professionals routinely used AI during this study period. Physicians and men were more likely to report frequent AI use, and frequent AI users more often reported positive sentiments about AI’s future impacts on pay, enjoyment, and productivity at work. The youngest professionals (≤29 years) were less engaged and more skeptical about AI’s future benefits. These findings highlight a gap between AI’s promise and medical practice, as adoption varies by role, experience, and demographics.